A viral race for primacy: co-infection of a natural pair of low and highly pathogenic H7N7 avian influenza viruses in chickens and embryonated chicken eggs. Issue 1 (December 2018) - Graaf, Annika; Ulrich, Reiner; Maksimov, Pavlo; Scheibner, David; Koethe, Susanne; Abdelwhab, Elsayed; Mettenleiter, Thomas; Beer, Martin; Harder, Timm
Abstract Highly pathogenic avian influenza virus (HPAIV) infection in poultry caused devastating mortality and economic losses. HPAIV of subtypes H5 and H7 emerge from precursor viruses of low pathogenicity (LP) by spontaneous mutation associated with a shift in the susceptibility of the endoproteolytic cleavage site of the viral hemagglutinin protein from trypsin- to furin-like proteases. A recently described natural pair of LP/HP H7N7 viruses derived from two spatio-temporally linked outbreaks in layer chickens was used to study how a minority of mutated HP virions after de novo generation in a single host might gain primacy. Co-infection experiments in embryonated eggs and in chickens were conducted to investigate amplification, spread and transmissionof HPAIV within a poultry population that experiences concurrent infection by an antigenically identical LP precursor virus. Simultaneous LPAIV co-infection (inoculum dose of 106 egg-infectious dose 50% endpoint (EID50 )/0.5 mL) withincreasing titers of HPAIV from 101 to 105.7 EID50 /0.5 mL) had a significant impeding impact on HP H7 replication, viral excretion kinetics, clinical signs and histopathological lesions (in vivo) and on embryo mortality (in ovo). LP/HP co-infected chickens required a hundredfold higher virus dose (HPAIV inoculum of 105 EID50 ) compared to HPAIV mono-infection (HPAIV inoculum of 103 EID50 ) to develop overt clinical signs, mortality and virus spread to uninfected sentinels. Escape and spread of HP phenotypes after de novo generation in an index host may therefore be highly precarious due to significant competition with co-circulating LP precursor virus.